KONTEKSTUALISASI REFORMASI BIROKRASI ASPEK KULTURAL PEMERINTAH KABUPATEN KUTAI KARTANEGARA: PERSPEKTIF DYNAMIC GOVERNANCE - Yani, Fipin Indera (Magister Administrasi Publik FISIP Universitas Mulawarman, 2023)
This research aims to analyze the implementation of cultural aspects of bureaucratic reform and the obstacles faced by cultural aspects of bureaucratic reform in Kutai Kartanegara Regency, using a Dynamic Governance approach, namely Thinking Ahead Capacity, Thinking Again Capacity, Thungking Across Capacity, Human Resources and Supporting Structures, and the processes involved agile. This research uses a hybrid concurrent triangulation method. The research results show that bureaucratic reform in Kutai Kartanegara Regency uses an inward-looking (administrative-procedural) approach causing bureaucratic reform to be unresponsive and adaptive to external demands, namely community welfare. The Thinking Ahead capacity shows that heads of regional apparatus have an important role in sharing new ideas based on data which will influence the level of success of programs and activities. The Thinking Again capacity shows that leadership attention to a data-based evaluation culture is still low. The obstacle to doing Thinking Across is the worry that it will have legal implications. Factors inhibiting capable human resources are too many levels of hierarchy, rules and procedures, causing staff not to dare to take the initiative to innovate and factors inhibiting agile processes are not all employees understanding standard operational procedures for performance reporting and the leadership’s role in discussing performance achievements with staff is not yet optimal.